2013
DOI: 10.1103/physreve.87.042911
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of traveling waves with mass-with-mass defects within a Hertzian chain

Abstract: We study the dynamic response of a granular chain of particles with a resonant inclusion (i.e., a particle attached to a harmonic oscillator, or a mass-with-mass defect). We focus on the response of granular chains excited by an impulse, with no static precompression. We find that the presence of the harmonic oscillator can be used to tune the transmitted and reflected energy of a mechanical pulse by adjusting the ratio between the harmonic resonator mass and the bead mass. Furthermore, we find that this syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Here and in what follows, n ranges from −N to N . For the analysis purposes it is convenient to rescale the governing equations (1) and the initial conditions (2) by introducing dimensionless displacementsū n ,v 0 and timet related to the original variables via [18,21]…”
Section: The Modelmentioning
confidence: 99%
“…Here and in what follows, n ranges from −N to N . For the analysis purposes it is convenient to rescale the governing equations (1) and the initial conditions (2) by introducing dimensionless displacementsū n ,v 0 and timet related to the original variables via [18,21]…”
Section: The Modelmentioning
confidence: 99%
“…Admittedly, both of these realizations were chiefly linear (in the presence of externally imposed pre-compression of the chain) and aiming to illustrate the remarkable meta-material type properties that these systems possess. Yet, while a MwM nonlinear prototype was also demonstrated in [61], it was a different type of experiment that very recently realized highly nonlinear propagation in a locally resonant granular system [62]. In particular, the experiment of [62] built a so-called woodpile configuration consisting of orthogonally stacked rods (every second rod is aligned, in this alternating 0-90 degree configuration) and demonstrated that the internal vibrations of the rods can play the role of the local resonator within the granular chain.…”
Section: Introductionmentioning
confidence: 99%
“…An additional possibility which would avoid the complications (slow tail decay in Fourier space) of the Fourier calculation proposed above would be to revert (37) and (38) into real space. That would reduce the number of modes needed for an accurate computation of the solution.…”
Section: A the Pego-english Approach And The Existence Of Nanopteramentioning
confidence: 99%
“…A typical example of the result of the iteration scheme of (37) and (38) is given in Figures 14 and 15 for the case of ν = 0.05. Figure 14 illustrates the result of the iterative scheme of the equations towards the acquisition of a traveling wave solution.…”
Section: A the Pego-english Approach And The Existence Of Nanopteramentioning
confidence: 99%